Adherence to Levothyroxine Treatment Among Patients With Hypothyroidism: A Northeastern Italian Survey - Cappelli, Carlo; Castello, Roberto; Marini, Fiorella; Paoletta, Agostino; Marchetti, Massimo; Saullo, Maura; Cristiano, Alessandra; Pirola, Ilenia; Gandossi, Elena; Ferlin, Alberto; Castellano, Maurizio (Frontiers in Endocrinology, 2018)
Background: A significant number of patients showed sub-optimal adherence to LT4 therapy, mainly due to the fact that they had to postpone their breakfast of at least 30 minutes. The aim of this observational cross-sectional study was to assess the therapeutic compliance of patients on LT4 treatment and secondly to verify the preference of a lifetime treatment in tablets or liquid formulation. Patients and Methods: To all the participant (ambulatory care patients had to be eighteen or older, affected by hypothyroidism on LT4 substitutive treatment both in tablet or liquid solution) was administered the eight-item Morisky Medication Adherence Scale (MMAS-8). The MMAS-8 questionnaire has been supplemented with other three items in order to specifically evaluate medication preference between tablet and liquid LT4 formulation for long life treating. Results: A total of 320 patients (272 female) with median age of 47.9±15.6 yrs (range 20-78) completed the MMAS-8 questionnaire. We showed a high adherence (87% of the subjects) to therapeutic compliance both for patients on tablets than those on liquid LT4 formulation, although significant difference are emerged. Patients assuming LT4 in tablet forgot more frequently medication(s) (p<0.001), felt hassled about sticking to their treatment plan (p<0.001) and had difficulty to remember to take all their medication(s) (p<0.001) than those on liquid LT4 treatment. Conclusions: We showed a high adherence to levothyroxine treatment both for tablets than for liquid formulation. The possibility to take LT4 treatment at breakfast represent the best convenience for the majority of patients.